Preliminary evaluation of kaolinitic waste from kaolin processing industries as a raw material for the production of a highly reactive metakaolinite - Barata, Márcio Santos (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This work has assessed potential uses of kaolinitic waste from kaolin processing industries as a raw material for the production of a highly reactive metakaolinite. The mineralogical characteristics of both this residue and also of the metakaolinite have been determined by X-ray diffraction and by differential thermal analysis. The metakaolinite pozzolanic activity was measured using Portland cement mortars. Resulting effects derived from metakaolinite incorporation on concrete were evaluated through compressive strength and water absorption tests. A 10% value was adopted for this incorporation procedure, whereas water/binder ratios chosen were 0.39, 0.47 and 0.65. Besides the mixtures, reference and silica fume concretes were also moulded. The metakaolinite pozzolanic activity index obtained was 103%, which is similar to that of silica fume. Metakaolinite concretes showed higher compressive strength values than that of reference concretes and similar to that of silica fume concretes. Concerning capillary absorption, metakaolinite concretes exhibited water penetration rates ranging from 0.73 to 0.98 mm/h1/2, similar to those of silica fume concretes and significantly lower to those of reference concretes. Therefore, this study has demonstrated that this kaolinitic waste is an excellent raw material for high reactivity metakaolinite production.